Low oxytocin levels are broadly associated with more pronounced psychopathology in anorexia nervosa with primarily restricting but not binge/purge eating behavior - Plessow, Franziska; Galbiati, Francesca; Eddy, Kamryn T.; Misra, Madhusmita; Miller, Karen K.; Klibanski, Anne; Aulinas, Anna; Lawson, Elizabeth A. (Frontiers in Endocrinology, 2023)
Objective: Anorexia nervosa (AN) is commonly associated with depression, anxiety, and deficits in socioemotional functioning. Basal levels of oxytocin, a neurohormone with antidepressant, anxiolytic, and prosocial properties, are low in women with AN. However, the relationship between oxytocin and psychopathology of AN/atypical AN has not been examined in individuals with primarily food restriction (AN/AtypAN-R) or those with restriction plus binge/purge behaviors (AN/AtypAN-BP) alone, which is important to further elucidate the neurobiology of different AN presentations. We investigated whether oxytocin levels are related to eating, affective, and socioemotional psychopathology in women with AN/AtypAN-R and separately AN/AtypAN-BP. Methods: In a cross-sectional study of 53 women with low-weight AN or atypical AN based on DSM-5 (AN/AtypAN-R: n=21, AN/AtypAN-BP: n=32), we obtained fasting serum oxytocin levels and self-report measures of psychopathology, including the Eating Disorder Examination–Questionnaire (EDE-Q), Beck Depression Inventory-IA (BDI), State-Trait Anxiety Inventory (STAI), and Toronto Alexithymia Scale (TAS-20). Results: In individuals with AN/AtypAN-R, oxytocin levels were negatively associated with eating psychopathology (EDE-Q Global Score: r=-0.49, p=0.024), depressive and anxiety symptoms (BDI Total Score: r=-0.55, p=0.009; STAI Trait Score: r=-0.63, p=0.002), and socioemotional symptoms (TAS-20 Difficulty Identifying Feelings Score: r=-0.49, p=0.023). In contrast, in those with AN/AtypAN-BP oxytocin levels were negatively associated with depressive symptoms only (BDI Total Score: r=-0.52, p=0.049). Conclusions: These findings support the notion that AN/AtypAN-R and AN/AtypAN-BP might have divergent underlying neurobiology. Understanding these differences is crucial to develop targeted treatments for a population with high levels of chronicity, for which no specific pharmacological treatments are currently available.